Cascading Effects of Climate Change: Do Hurricane‐damaged Forests Increase Risk of Exposure to Parasites?. (29th October 2013) - Behie, Alison M.; Kutz, Susan; Pavelka, Mary S.
Abstract Increased parasitism in animals in disturbed habitats is often understood to be the result of increased disease susceptibility due to low food availability resulting in nutritionally stressed and immunocompromised individuals. Such habitat change, however, might also lead to increased exposure to disease. In this article, we test measures of susceptibility and exposure to explain the prevalence and intensity of directly and indirectly transmitted helminths in black howler monkeys (Alouatta pigra) following a hurricane in Belize. None of these parasites were predicted by direct measures of susceptibility (as measured by fruit consumption and fecal cortisol levels). Rather, directly transmitted parasites (Trichuris sp. and strongylid type eggs.) were predicted by host density and group size, both measures of exposure. Similarly, only the consumption of Cecropia peltata, a fast growing pioneer that has a mutualistic relationship with ants predicted levels of the indirectly transmitted trematode Controrchis spp., also suggesting exposure. Cecropia peltata also increased in density post‐hurricane, was high in digestible protein, sugar, and salt and eaten by monkeys more frequently than predicted based on distribution. These data suggest that in this hurricane‐damaged forest the ingestion of this abundant and nutritious pioneer species increased exposure of the monkeys to Controrchis through ingestion of ant intermediate hosts. These results may point to a pattern true of pioneer species in general, leaving animals in disturbed forests with higher levels of parasitism as a result of changes to forest structure. As severe weather events are expected to increase, this suggests a cascading effect of climate change on ecosystem interactions and disease ecology.